Teachers’ Lived Experiences of Principal Leadership in Supporting the Learning Process: A Phenomenological Study in an Elementary School - Iis Syahdli (Journal of Innovation in Teaching and Instructional Media, 2026)
This study aims to explore teachers’ lived experiences of principal leadership in supporting the learning process. This study was conducted at SDN 32 Bengkulu Selatan. This study employed a qualitative phenomenological design and also literature review. Six teachers were purposively selected based on teaching experience and active school involvement. Data were collected through semi-structured interviews and analyzed using thematic analysis (coding, categorization, interpretation). The findings revealed three key leadership practices: instructional support through classroom supervision and constructive feedback; participatory decision-making that fosters teacher engagement; and motivational support that enhances teacher commitment and performance. These practices significantly contribute to improving teaching and learning quality. This study contributes to educational leadership literature by providing context-based insights into how leadership is experienced by teachers. Practically, the findings suggest that principals should adopt supportive and participatory leadership approaches, while policymakers should design leadership development programs aligned with school needs.